Forced response of a high-static-low-dynamic (HSLD) stiffness isolator with active stiffness control / Muhajir Ab Rahim, Mohd Azmi Yunus and Muhamad Norhisham Abdul Rani - Ab Rahim, Muhajir; Yunus, Mohd Azmi; Abdul Rani, Muhamad Norhisham (UiTM Press, 2024)
The High-Static-Low-Dynamic (HSLD) stiffness vibration isolators have been exploited in many engineering applications due to its capability in having a wider isolation bandwidth, while maintaining the high static load capacities. However, it will lead to a large payload oscillation at the static equilibrium position, if the source of vibration is an oscillating force originating within the payload. In this case, the considerably large resultant motion of the payload will change the system nonlinearity. An active stiffness control for reducing the displacement amplitude of the payload oscillation subjected to a harmonic force excitation is proposed in this paper. The dynamic model of an actively stiffened HSLD stiffness isolator is introduced, and the approximate analytical expression for forced response is obtained using the Harmonic Balance Method (HBM). The obtained forced response curve has demonstrated that the active stiffness control is able to reduce the system’s force response, particularly at low frequencies with an approximation of 50%. The nonlinearity of the system becomes smaller as the active stiffness control is applied.